The effect of storage conditions and washing on microplastic release from food and drink containers. (June 2022) - Hee, Yet Yin; Weston, Keith; Suratman, Suhaimi
Abstract: Microplastic production due to storage and washing for re-use for commonly used food and drink containers in eat-in and takeaway catering was quantified and characterised using a combination of Nile Red staining, Scanning Electron Microscope imaging and infrared microscopy. The containers received 'hot' (water at 95 ºC added) or 'cold' (water with ice added) storage treatments for 1 or 5 h dependent on typical usage. All treatments resulted in microplastic production. Plastics listed by the manufacturer as being used for the production of the containers were identified as produced microplastics with additional types of microplastic also produced. Nile Red staining showed an average microplastic production of 176 particles/L (p/L) with the higher production (261 p/L) from takeaway polystyrene boxes due to its fibrous structure. Higher microplastic production also occurred in 'hot' treatment (192 p/L) relative to 'cold' treatment (90 p/L) for takeaway high-density polyethylene bags. Repeated washing of an eat-in melamine bowl showed microplastic production was an order of magnitude greater after washing 100 times (394 p/L) relative to a bowl washed once (18 p/L). Using the MP production measured in this study we estimate an individual's annual microplastic ingestion in Southeast Asian countries to typically be ~195, 000 microplastic particles from takeaway/eat-in food and drink storage. MP production from food and drink storage and washing therefore represents a key source of microplastic contamination in the human diet. Graphical Abstract: ga1 Highlights: All containers produced microplastics from 10 to 710 particles/L. Higher storage temperature and washing caused increased microplastic production. Microplastic production was not correlated with storage time. Manufacturer labelling did not fully represent the microplastic types produced. A weekly takeaway meal results in an annual ingestion of up to 18, 500 microplastic particles.